Malcolm X's Michigan worldview : an exemplar for contemporary black studies - Edozie, Rita Kiki; Stokes, Curtis; Boyd, Herb, 1938- (Michigan State University Press, 2015)
"The provocative debate about Malcolm X's legacy that emerged after the publication of Manning Marable's 2011 biography raised critical questions about the revolutionary Black Nationalist's importance to American and world affairs: What was Malcolm's association with the Nation of Islam? How should we interpret Malcolm's discourses? Was Malcolm antifeminist? What is Malcolm's legacy in contemporary public affairs? How do Malcolm's early childhood experiences in Michigan shape and inform his worldview? Was Malcolm trending toward socialism during his final year? Malcolm X's Michigan Worldview responds to these questions by presenting Malcolm's subject as an iconography used to deepen understanding of African descendant peoples' experiences through advanced research and disciplinary study. A Black studies reader that uses the biography of Malcolm X both to interrogate key aspects of the Black world experience and to contribute to the intellectual expansion of the discipline, the book presents Malcolm as a Black subject who represents, symbolizes, and associates meaning with the Black/Africana studies discipline. Through a range of multidisciplinary prisms and themes including discourse, race, culture, religion, gender, politics, and community, this rich volume elicits insights about the Malcolm iconography that contribute to the continuous formulation, deepening, and strengthening of the Black studies discipline."--Provided by publisher